A combination of Al-doped ZnO and a conjugated polyelectrolyte interlayer for small molecule solution-processed solar cells with an inverted structure - Min, Jie; Zhang, Hong; Stubhan, Tobias; Luponosov, Yuriy N.; Kraft, Mario; Ponomarenko, Sergei A.; Ameri, Tayebeh; Scherf, Ullrich; Brabec, Christoph (Journal of Materials Chemistry A, 2013)
We successfully demonstrate a smart strategy to use aluminum doped ZnO (AZO) and the thiophene-based conjugated polyelectrolyte P3TMAHT as an interfacial layer in small molecule solution-processed inverted solar cells. Modification of AZO with a thin P3TMAHT layer increases the photovoltaic properties of the inverted cell as a result of reduction in the work function of the cathode with well aligned frontier orbital energy levels for efficient charge transport and reduced surface recombination. The inverted device achieved 16% performance improvement dominantly by recapturing part of the Voc losses when going from conventional to the inverted architecture. In addition, the inverted device using the AZO/P3TMAHT interlayer shows improved device stability in air compared to conventional devices.
Keywords: Aluminum-doped ZnO; Conjugated polyelectrolytes; Frontier orbital energies; Inverted architectures; Inverted solar cells; Photovoltaic property; Solution-processed; Surface recombinations Engineering controlled terms: Molecules; Polyelectrolytes; Zinc oxide Engineering main heading: Solar cells

Air-processed organic tandem solar cells on glass: Toward competitive operating lifetimes - Adams, Jens; Spyropoulos, Georgios; Salvador, Michael Filipe; Li, Ning; Strohm, Sebastian; Lucera, Luca; Langner, Stefan; Machui, Florian; Zhang, Hong; Ameri, Tayebeh; Voigt, Monika M.; Krebs, Frederik C.; et al. (Energy and Environmental Science, 2015)
Photovoltaic devices based on organic semiconductors (OPVs) hold great promise as a cost-effective renewable energy platform because they can be processed from solution and deposited on flexible plastics using roll-to-roll processing. Despite important progress and reported power conversion efficiencies of more than 10% the rather limited stability of this type of devices raises concerns towards future commercialization. The tandem concept allows for both absorbing a broader range of the solar spectrum and reducing thermalization losses. We designed an organic tandem solar cell with an inverted device geometry comprising environmentally stable active and charge-selecting layers. Under continuous white light irradiation, we demonstrate an extrapolated, operating lifetime in excess of one decade. We elucidate that for the current generation of organic tandem cells one critical requirement for long operating lifetimes consists of periodic UV light treatment. These results suggest that new material approaches towards UV-resilient active and interfacial layers may enable efficient organic tandem solar cells with lifetimes competitive with traditional inorganic photovoltaics.

A Series of Pyrene-Substituted Silicon Phthalocyanines as Near-IR Sensitizers in Organic Ternary Solar Cells - Ke, Lili; Min, Jie; Adam, Matthias; Gasparini, Nicola; Hou, Yi; Perea, Jose Dario; Chen, Wei; Zhang, Hong; Fladischer, Stefanie; Sale, Anna Chiara; Spiecker, Erdmann; Tykwinski, Rik; et al. (Advanced Energy Materials, 2016)
An attractive method to broaden the absorption bandwidth of polymer/fullerene-based bulk heterojunction (BHJ) solar cells is to blend near infrared (near-IR) sensitizers into the host system. Axial substitution of silicon phthalocyanines (Pcs) opens a possibility to modify the chemical, thermodynamic, electronic, and optical properties. Different axial substitutions are already designed to modify the thermodynamic properties of Pcs, but the impact of extending the π-conjugation of the axial ligand on the opto-electronic properties, as a function of the length of the alkyl spacer, has not been investigated yet. For this purpose, a novel series of pyrene-substituted silicon phthalocyanines (SiPc-Pys) with varying lengths of alkyl chain tethers are synthesized. The UV-vis and external quantum efficiency (EQE) results exhibit an efficient near IR sensitization up to 800 nm, clearly establishing the impact of the pyrene substitution. This yields an increase of over 20% in the short circuit current density (J ) and over 50% in the power conversion efficiency (PCE) for the dye-sensitized ternary device. Charge generation, transport properties, and microstructure are studied using different advanced technologies. Remarkably, these results provide guidance for the diverse and judicious selection of dye sensitizers to overcome the absorption limitation and achieve high efficiency ternary solar cells.
Keywords: Absorption limitations; Charge transport; Near-IR sensitizers; Silicon phthalocyanine; Ternary solar cells

A solution-processed barium hydroxide modified aluminum doped zinc oxide layer for highly efficient inverted organic solar cells - Zhang, Hong; Stubhan, Tobias; Li, Ning; Turbiez, Mathieu; Matt, Gebhard; Ameri, Tayebeh; Brabec, Christoph (Journal of Materials Chemistry A, 2014)
Inverted organic solar cells (iOSCs) with air stable interface materials and top electrodes and an efficiency of 6.01% are achieved by inserting a barium hydroxide (Ba(OH)) layer between the aluminum doped zinc oxide (AZO) electron extraction layer and the active layer. A low bandgap diketopyrrolopyrrole-quinquethiophene alternating copolymer (pDPP5T-2) and phenyl-C61-butyric acid methyl ester (PCBM) were chosen as the active layer compounds. Compared to the control device without Ba(OH), insertion of a few nm thick Ba(OH) layer results in an enhanced V of 10%, J of 28%, FF of 28% and PCE of 80%. Modification of AZO with a solution processed low-cost Ba(OH) layer increased the efficiency of the inverted device by dominantly reducing the energy barrier for electron extraction from PCBM, and consequently, reduced charge recombination is observed. The drastic improvement in device efficiency and the simplicity of fabrication by solution processing suggest Ba(OH) as a promising and practical route to reduce interface induced recombination losses at the cathode of organic solar cells.
Keywords: Aluminum doped zinc oxide layers; Barium hydroxide; Inverted organic solar cells; Solution-processed

A universal interface layer based on an amine-functionalized fullerene derivative with dual functionality for efficient solution processed organic and perovskite solar cells - Azimi, Seyed Hamed; Ameri, Tayebeh; Ameri, Tayebeh; Zhang, Hong; Hou, Yi; Ramírez Quiroz, César Omar; Min, Jie; Hu, Mengyao; Zhang, Zhi-Guo; Przybilla, Thomas; Matt, Gebhard; Spiecker, Erdmann; et al. (Advanced Energy Materials, 2015)
The successful application of an effective dipolar interface layer based on an amine functionalized fullerene derivative (DMAPA-C60) is reported for the perovskite and organic photovoltaic devices. The incorporation of DMAPA-C60 facilitates a favorable energy level alignment, and results in enhanced mobility-lifetime (μt) produc
Keywords: energy level alignment; mobility-lifetime products; organic photovoltaic devices; perovskite solar cells

Environmentally Printing Efficient Organic Tandem Solar Cells with High Fill Factors: A Guideline Towards 20% Power Conversion Efficiency - Li, Ning; Baran, Derya; Spyropoulos, George D.; Zhang, Hong; Berny, Stephane; Turbiez, Mathieu; Ameri, Tayebeh; Krebs, Frederik C.; Brabec, Christoph (Advanced Energy Materials, 2014)
The tandem concept involves stacking two or more cells with complementary absorption spectra in series or parallel connection, harvesting photons at the highest possible potential. It is strongly suggested that the roll-to-roll production of organic solar cells will employ the tandem concept to enhance the power conversion efficiency (PCE). However, due to the undeveloped deposition techniques, the challenges in ink formulation as well as the lack of commercially available high performance active materials, roll-to-roll fabrication of highly efficient organic tandem solar cells currently presents a major challenge. The reported high PCE values from lab-scale spin-coated devices are, of course, representative, but not helpful for commercialization. Here, organic tandem solar cells with exceptionally high fill factors and PCE values of 7.66% (on glass) and 5.56% (on flexible substrate), which are the highest values for the solution-processed tandem solar cells fabricated by a mass-production compatible coating technique under ambient conditions, are demonstrated. To predict the highest possible performance of tandem solar cells, optical simulation based on experimentally feasible values is performed. A maximum PCE of 21% is theoretically achievable for an organic tandem solar cell based on the optimized bandgaps and achieved fill factors.
Keywords: flexible electronics; large-scale production; organic photovoltaics; organic solar cells; solution processing

Exploring the Limiting Open-Circuit Voltage and the Voltage Loss Mechanism in Planar CH3NH3PbBr3 Perovskite Solar Cells - Chen, Shi; Hou, Yi; Chen, Haiwei; Richter, Moses; Guo, Fei; Kahmann, Simon; Tang, Xiaofeng; Stubhan, Tobias; Zhang, Hong; Li, Ning; Gasparini, Nicola; Ramírez Quiroz, César Omar; et al. (Advanced Energy Materials, 2016)
Perovskite solar cells based on CHNHPbBr with a band gap of 2.3 eV are attracting intense research interests due to their high open-circuit voltage (V) potential, which is specifically relevant for the use in tandem configuration or spectral splitting. Many efforts have been performed to optimize the V of CHNHPbBr solar cells; however, the limiting V (namely, radiative V:V) and the corresponding ΔV (the difference between V and V) mechanism are still unknown. Here, the average V of 1.50 V with the maximum value of 1.53 V at room temperature is achieved for a CHNHPbBr solar cell. External quantum efficiency measurements with electroluminescence spectroscopy determine the V of CHNHPbBr cells with 1.95 V and a ΔV of 0.45 V at 295 K. When the temperature declines from 295 to 200 K, the obtained V remains comparably stable in the vicinity of 1.5 V while the corresponding ΔV values show a more significant increase. Our findings suggest that the V of CHNHPbBr cells is primarily limited by the interface losses induced by the charge extraction layer rather than by bulk dominated recombination losses. These findings are important for developing strategies how to further enhance the V of CHNHPbBr-based solar cells.
Keywords: CH3NH3PbBr3 solar cells; interface materials based losses; nonradiative recombination losses; open-circuit voltage

Extending the environmental lifetime of unpackaged perovskite solar cells through interfacial design - Chen, Haiwei; Hou, Yi; Halbig, Christian Eberhard; Chen, Shi; Zhang, Hong; Li, Ning; Guo, Fei; Tang, Xiaofeng; Gasparini, Nicola; Levchuk, Ievgen; Kahmann, Simon; Ramírez Quiroz, César Omar; et al. (Journal of Materials Chemistry A, 2016)
Solution-processed oxo-functionalized graphene (oxo-G) is employed to substitute hydrophilic PEDOT:PSS as an anode interfacial layer for perovskite solar cells. The resulting devices exhibit a reasonably high power conversion efficiency (PCE) of 15.2% in the planar inverted architecture with oxo-G as a hole transporting material (HTM), and most importantly, deploy the full open-circuit voltage (V) of up to 1.1 V. Moreover, oxo-G effectively slows down the ingress of water vapor into the device stack resulting in significantly enhanced environmental stability of unpackaged cells under illumination with 80% of the initial PCE being reached after 500 h. Without encapsulation, ∼60% of the initial PCE is retained after ∼1000 h of light soaking under 0.5 sun and ambient conditions maintaining the temperature beneath 30 °C. Moreover, the unsealed perovskite device retains 92% of its initial PCE after about 1900 h under ambient conditions and in the dark. Our results underpin that controlling water diffusion into perovskite cells through advanced interface engineering is a crucial step towards prolonged environmental stability.
Keywords: Engineering controlled terms: Cell engineering; Conducting polymers; Open circuit voltage; Perovskite; Slow light; Solar cells Environmental stability; Functionalized graphene; High power conversion; Hole-transporting materials; Interface engineering; Interfacial design; Inverted architectures; Solution-processed Engineering main heading: Perovskite solar cells

Improved High-Efficiency Perovskite Planar Heterojunction Solar Cells via Incorporation of a Polyelectrolyte Interlayer - Zhang, Hong; Azimi, Seyed Hamed; Hou, Yi; Ameri, Tayebeh; Przybilla, Thomas; Spiecker, Erdmann; Kraft, Mario; Scherf, Ullrich; Brabec, Christoph (Chemistry of Materials, 2014)
No abstract available for this article

Inverted, Environmentally Stable Perovskite Solar Cell with a Novel Low-Cost and Water-Free PEDOT Hole-Extraction Layer - Hou, Yi; Zhang, Hong; Chen, Wei; Chen, Shi; Ramírez Quiroz, César Omar; Azimi, Seyed Hamed; Osvet, Andres; Matt, Gebhard; Zeira, Eitan; Seuring, Jan; Kausch-Busies, Nina; Loevenich, Wilfried; et al. (Advanced Energy Materials, 2015)
A power conversion efficiency of 11.8% is demonstrated for planar perovskite solar cell based on acid water-free poly(3,4-ethylenedioxythiophene) (PEDOT) as the hole-transporting layer. This efficiency is further improved to 14.2% using a pH neutralized PEDOT, which reduces the sub-gap defects at the surface of perovskite. All the active layers reported are solution-processed at temperatures below 140 °C making it compatible with roll-to-roll production.
Keywords: low-temperature processing; perovskite solar cells; stabilities; water-free poly(3; 4-ethylenedioxythiophene)

Overcoming Electrode-Induced Losses in Organic Solar Cells by Tailoring a Quasi-Ohmic Contact to Fullerenes via Solution-Processed Alkali Hydroxide Layers - Zhang, Hong; Shallcross, R. Clayton; Li, Ning; Stubhan, Tobias; Hou, Yi; Chen, Wei; Ameri, Tayebeh; Turbiez, Mathieu; Armstrong, Neal R.; Brabec, Christoph (Advanced Energy Materials, 2016)
It is shown that the performance of inverted organic solar cells can be significantly improved by facilitating the formation of a quasi-ohmic contact via solution-processed alkali hydroxide (AOH) interlayers on top of n-type metal oxide (aluminum zinc oxide, AZO, and zinc oxide, ZnO) layers. AOHs significantly reduce the work function of metal oxides, and are further proven to effectively passivate defect states in these metal oxides. The interfacial energetics of these electron collecting contacts with a prototypical electron acceptor (C) are investigated to reveal the presence of a large interface dipole and a new interface state between the Fermi energy and the C highest occupied molecular orbital for AOH-modified AZO contacts. These novel interfacial gap states are a result of ground-state electron transfer from the metal hydroxide-functionalized AZO contact to the adsorbed molecules, which are hypothesized to be electronically hybridized with the contact. These interface states tail all the way to the Fermi energy, providing for a highly n-doped (metal-like) interfacial molecular layer. Furthermore, the strong "light-soaking" effect is no longer observed in devices with a AOH interface. Solution-processed alkali hydroxides significantly reduce the work function of metal oxides, such as zinc oxide or aluminum zinc oxide (AZO), and are further proven to effectively passivate defect states in these metal oxides. The interface states with alkali hydroxide-modified AZO contacts tail all the way to the Fermi energy, providing for a highly n-doped (metal-like) interfacial molecular layer.
Keywords: alkali hydroxide; interfacial layers; organic solar cells; solution processing

Overcoming the Interface Losses in Planar Heterojunction Perovskite-Based Solar Cells - Hou, Yi; Chen, Wei; Baran, Derya; Stubhan, Tobias; Luechinger, Norman A.; Hartmeier, Benjamin; Richter, Moses; Min, Jie; Chen, Shi; Ramírez Quiroz, César Omar; Li, Ning; Zhang, Hong; et al. (Advanced Materials, 2016)
An experiment was conducted to demonstrate that low-temperature processed NiO-based nanocrystal ink (LT-NiO) has the potential to form an almost loss-free hole selective interface for flat heterojunction perovskite-based solar cells. First, The patterned ITO substrates were ultrasonic cleaned with acetone and isopropanol for 10 min each. On cleaned ITO substrate, a dense and smooth layer of LT-NiO was deposited by spin coating and followed by annealing at 70?230°C for 10 min in air to remove organic components. The as-prepared perovskite precursor solution was filtered using 0.45 μm PTFE syringe filter and coated onto the ITO/LT-NiO substrate at a speed of 4000 r.p.m. for 35 s. J-V characteristics of all the devices were measured using a source measurement unit from BoTest. FTPS:FTPS-EQE measurements were carried out using a Vertex 70 from Brucker optics, equipped with QTH lamp, quartz beam splitter and external detector option. A major improvement in open circuit voltage is found by replacing PEDOT:PSS with LT-NiO. A detailed analysis reveals that LT-NiO significantly reduces non-radiative recombination at the PEDOT:PSS/perovskite interface and further enhances the radiative LED efficiency towards unity which brings open circuit voltage closer to the radiative limit.
Keywords: low temperature processing; nickel oxide; non-radiative voltage loss; perovskite solar cells

Panchromatic ternary/quaternary polymer/fullerene BHJ solar cells based on novel silicon naphthalocyanine and silicon phthalocyanine dye sensitizers - Ke, Lili; Gasparini, Nicola; Min, Jie; Zhang, Hong; Adam, Matthias; Rechberger, Stefanie; Forberich, Karen; Zhang, Chaohong; Spiecker, Erdmann; Tykwinski, Rik; Brabec, Christoph; Ameri, Tayebeh (Journal of Materials Chemistry A, 2017)
More efficient light harvesting throughout the whole solar spectrum by introducing third and fourth components offers a new pathway towards the development of high efficiency organic solar cells based on polymer/fullerene blends. Recently, dye molecules have been utilized as promising light harvesting photosensitizers in the near-IR region. Herein, we report the design, synthesis and application of a novel silicon naphthalocyanine (SiNC-1) as an efficient photosensitizer in single dye ternary devices as well as in multi-colored co-sensitized quaternary devices, incorporating a silicon phthalocyanine (SiPC-0 or SiPC-1) as the fourth component to complement the spectral absorption of the SiNC-1. The dominant complex charge transfer/transport mechanism behind the enhanced photosensitivity of the ternary blend has been investigated by means of electrical, optical, and advanced characterization techniques. External quantum efficiency (EQE) measurements on multi-colored dye sensitized devices covering the UV-vis as well as near-IR regions from 350 up to 900 nm outline apparent signal characteristics of each single dye, corroborating the effective contribution of both SiPC and SiNC dyes to enhancing the short-circuit current density (J). Our results further illustrate the potential of the multi-colored dye sensitization concept as a powerful approach to mitigate the non-ideal optical absorption normally encountered in organic-based optoelectronic devices.
Keywords: Engineering controlled terms: Charge transfer; Dye-sensitized solar cells; Efficiency; Electromagnetic wave absorption; Light absorption; Nitrogen compounds; Optoelectronic devices; Organic solar cells; Photosensitizers; Polymer blends; Polymer solar cells; Silicon; Solar cells Characterization techniques; Dye sensitization; External quantum efficiency; Light-harvesting; Naphthalocyanines; Phthalocyanine dyes; Signal characteristic; Spectral absorptions Engineering main heading: Silicon solar cells

Roll to roll compatible fabrication of inverted organic solar cells with a self-organized charge selective cathode interfacial layer - Zhang, Hong; Tan, Wan-Yi; Fladischer, Stefanie; Ke, Lili; Ameri, Tayebeh; Li, Ning; Turbiez, Mathieu; Spiecker, Erdmann; Zhu, Xu-Hui; Cao, Yong; Brabec, Christoph (Journal of Materials Chemistry A, 2016)
We successfully demonstrate a simple approach to printing efficient, inverted organic solar cells (OSCs) with a self-organized charge selective cathode interface layer based on the small-molecule Phen-NaDPO. Different from previous studies, Phen-NaDPO molecules were blended into a polymer/fullerene blend, comprising a low bandgap diketopyrrolopyrrole-quinquethiophene alternating copolymer pDPP5T-2 and phenyl-C-butyric acid methyl ester (PCBM), and processed by doctor blading in air. We observed a spontaneous, surface energy driven migration of Phen-NaDPO towards the ZnO interface and a subsequent formation of electron selective and barrier free extraction contacts. In the presence of 0.5 wt% Phen-NaDPO, a PCE of 5.4% was achieved for the inverted device based on an ITO/ZnO cathode. Notably, the photovoltaic performances remained at the same level with increasing the Phen-NaDPO concentration in the active layer from 0.25 to 1 wt%. Furthermore, this approach could be proven to effectively work with other cathodes such as bare ITO and ITO/AZO. The self-organization of Phen-NaDPO through spontaneous vertical phase separation is mainly attributed to its high surface energy and strong interaction with the cathode material. The present results highlight that a self-organized cathode interfacial material processed from a "ternary" active layer is fully compatible with the requirements for roll-to-roll fabrication of inverted organic solar cells.
Keywords: Engineering controlled terms: Butyric acid; Cathodes; Electrodes; Interfacial energy; Molecules; Organic solar cells; Phase separation Alternating copolymer; Cathode interfacial layers; Diketopyrrolopyrroles; High surface energy; Inverted organic solar cells; Photovoltaic performance; Roll-to-roll fabrication; Vertical phase separations Engineering main heading: Solar cells